Pengembangan Media Buku Teks Fikih Digital dalam Meningkatkan Hasil Belajar Peserta Didik di MAN 1 Mojokerto - Ahmad Yusam Thobroni; Dewi Masyithoh (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
The creation of digital textbooks is an attempt to address students' learning issues, particularly during the Covid-19 epidemic and post-pandemic new normal. The purpose of this research is to create digital fiqh textbooks and assess how successful it is in improving student learning results at MAN 1 Mojokerto. This is a research and development study, followed by an efficacy test employing a paired sample t-test through pre-test and post-test. The methods for generating a digital fiqh text book medium are as follows: (a) define stage (b) design stage (design); (c) develop stage (development); and (4) the disseminate stage. While the efficacy test revealed a considerable difference between the pre-test and post-test outcomes. Before using the media, the average value was 50.97 with a standard deviation of 18.929, and after using the media, the average value was 79.44 with a standard deviation of 10.473. The paired-sample test yielded a t-count value of 17.753, a t-table value of 2.02809, and a p-value of 0.000. The estimated t value is more than the t table, and the significance value is less than 0.05, indicating that learning using digital fiqh textbook learning media is more successful than learning without media.